(untitled) (REMUNOM, 2025)
In this review article, the typical morphologies and temperatures of a fire incident are addressed, analyzing the behavior of temperatures in each phase, comparing the periods of real fires, simulated fires and criteria standardized by national and international standards. Were evaluated the effects of fires on masonry walls and blocks, analyzing the behavior of this materials when subjected to high temperatures, also evaluating different methodologies for this type of study. At the end, the main pathologies suffered by masonry in fire situations are presented, in addition to highlighting the difficulties inherent to research of this nature.